2010
DOI: 10.1111/j.1365-2486.2009.02038.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biological invasions on forest carbon sequestration

Abstract: There has been a rapidly developing literature on the effects of some of the major drivers of global change on carbon (C) sequestration, particularly carbon dioxide (CO 2 ) enrichment, land use change, nitrogen (N) deposition and climate change. However, remarkably little attention has been given to one major global change driver, namely biological invasions. This is despite growing evidence that invasive species can dramatically alter a range of aboveground and belowground ecosystem processes, including those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 139 publications
(174 reference statements)
0
96
1
2
Order By: Relevance
“…Such shifts can serve as natural experiments which provide valuable insights into the myriad effects of individual plant species on ecosystem structure and function. A growing number of studies have shown that even single plant species can drive major changes in ecosystem wide C cycling (Bradley et al, 2006;Litton et al, 2008;Peltzer et al, 2010). In a survey of 94 experimental studies, invaded ecosystems on average had 83 % higher productivity and 117 % faster litter decomposition rates (Liao et al, 2008), often driven in part by consistent trait differences between invading species and native species.…”
Section: B Metcalfe Et Al: Plant Communities As Drivers Of Soil mentioning
confidence: 99%
See 1 more Smart Citation
“…Such shifts can serve as natural experiments which provide valuable insights into the myriad effects of individual plant species on ecosystem structure and function. A growing number of studies have shown that even single plant species can drive major changes in ecosystem wide C cycling (Bradley et al, 2006;Litton et al, 2008;Peltzer et al, 2010). In a survey of 94 experimental studies, invaded ecosystems on average had 83 % higher productivity and 117 % faster litter decomposition rates (Liao et al, 2008), often driven in part by consistent trait differences between invading species and native species.…”
Section: B Metcalfe Et Al: Plant Communities As Drivers Of Soil mentioning
confidence: 99%
“…(1) plant traits (Wardle et al, 2004;Cornwell et al, 2008;de Deyn et al, 2008), (2) plant invasions and range expansions (Peltzer et al, 2010), and (3) plant diversity (Hättenschwiler et al, 2005;Hooper et al, 2005). Finally, given the likelihood of future large scale shifts in the distribution, composition and diversity of plant communities driven by climate change (Neilson et al, 2005), we discuss the contrasting approaches taken by major models to simulate species effects on ecosystem C cycling Friedlingstein et al, 2006;Ostle et al, 2009;Reu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in temperatures and moisture regimes and increases in the incidence of chance events such as floods, droughts, and hurricanes could wipe out isolated populations of threatened species. Also, species invasions can be facilitated by climatic changes, and warming can have enormous consequences for carbon fluxes in forested ecosystems (Peltzer et al 2010).…”
Section: Carbon Sequestrationmentioning
confidence: 99%
“…土壤氮含量是陆生植物生长的主要限制因素 (Chapin et al,1986;Elser et al, 2010) (Feng et al, 2009;Peltzer et al, 2010)。因 此, 土壤氮可利用性能够影响种间竞争能力。 可利用性资源的增加能促进外来植物入侵 (He et al, 2012)。入侵植物一般具有较高的硝酸还原酶 活 性 , 因 此 多 具 有 嗜 氮 性 和 较 高 的 氮 利 用 效 率 (Feng et al, 2009;Penuelas et al, 2009;Peltzer et al, 2010), 往往能够耐受更贫瘠的土壤环境, 常表现为 较快的生长速度和较强的竞争能力 (Callaway et al, 2004;Bradley et al, 2010), 其种间竞争能力随氮元 素浓度的变化而变化 (Tilman et al, 1982;Grime, 2001;Peltzer et al, 2010)。 可见, 与本地植物种相比, 入侵植物表现出更强的氮利用性优势。 工业革命以来, 全球范围的大气氮沉降速率逐 步加快 (Reay et al, 2008;Maskell et al, 2010), 不断 提高土壤可利用性氮水平, 已经造成许多地区土壤 氮的富营养化 (Kardol et al, 2010;Garcia et al, 2011), 严重影响了陆地生态系统的生产力和稳定 性 (Phoenix et al, 2006;谢迎新等, 2010) (He et al, 2012;Martin et al, 2014;Mráz et al, 2014) (He et al, 2012), C. stoebe种群在不同入 侵地的竞争能力和竞争效果差异显著 (Ridenour et al, 2008;Reinhart & Rinella, 2011) …”
unclassified